Implications of Quantum Logic to the Notion of Transcendence - Manyahi, Jerome; Xavier, Francis (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This article attempts to study the notion of Transcendence from the perspective of Quantum Mechanics. The Laws of Physics reveal that nature is dynamic and it is understood in terms of mathematical models and relations. Uncertainty is a fundamental feature of the Quantum reality. Quantum structural pattern is the fundamental nature of reality, whether observable or unobservable. Transcendence in Quantum Mechanics is a dynamic concept which must be understood in terms of dynamic state. Transcendencein Quantum Mechanics is the process of uncovering deep treasures of the reality, which is dynamic. A movement toward the deeper reality of God is what is behind the notion of transcendence.